The influence of the social groups on the diet of Mexican university students - Lozano Marroquín, Cristina (Consorcio de Universidades Mexicanas A.C., 2021)
Food fulfills a primary social function as it implies structures, cultural values, and is even considered as a shared event that reflects social and collective well-being. Therefore, the aim of this study was to know the influence of the family on the healthy diet of university students in comparison with the diet of family, friends, and partner. The sample consisted of 223 university students from Mexico City. The instruments used were: Self-Monitoring of Eating Scale (SMES), Eating behavior questionnaire and the Instrument of Social Influence was based on Latané's theory of social impact and Kelman's theory of social influence. The results demonstrate a difference between the diet of men and women. Men reported eating more unhealthy foods, women have higher rates of self-monitoring and healthy food consumption.